30% supramolecular salicylic acid peels effectively treats acne vulgaris and reduces facial sebum. (25th February 2022) - Zhang, Lingzhao; Shao, Xinyi; Chen, Yangmei; Wang, Jiawei; Ariyawati, Asoka; Zhang, Yujie; Chen, Jiayi; Liu, Lin; Pu, Yihuan; Li, Yuxin; Chen, Jin
Abstract: Background: Acne is a chronic inflammatory skin disease with high incidence and recurrence. Aim: To study the efficacy of 30% supramolecular salicylic acid (SSA) in the treatment of acne, especially its effect on facial sebum secretion and the skin barrier. Methods: Chemical peeling treatment with SSA using self‐contrast was performed every 2 weeks for a total of four treatments in 25 patients. VISIA photographs and skin parameter measurements were recorded at every treatment, with a 2‐week follow‐up after the last treatment. We performed skin biopsy and immunohistochemical staining to detect sterol response element‐binding proteins (SREBPs), fatty acid synthase (FAS), and cyclooxygenase 2 (COX2), which are important factors involved in the regulation of sebum metabolism. Results: The global acne‐grading system (GAGS) score of patients with acne decreased with 30% SSA treatment. The sebum level in the nose ( p  < 0.001), chin ( p  < 0.001), left cheek ( p  < 0.05), and right cheek ( p  < 0.05) improved significantly with increasing number of treatments. The T‐zone sebum level ( p  < 0.001) improved more than the U‐zone ( p  < 0.01). The VISIA index porphyrin score also reduced ( p  < 0.001). Skin hydration ( p  < 0.001), transepidermal water loss (TEWL) ( p  < 0.05), and pH value ( p  < 0.01)—reflecting the skin barrier—were also improved. Immunohistochemistry showed decreased expression of SREBPs, FAS, and COX2. Conclusion: Peels with 30%SSA effectively treated acne and reduced facial sebum secretion without damaging the skin barrier. Reduction of sebum showed cumulative effect, which suggests that multiple 30%SSA chemical peels are beneficial to acne patients.